Instructional Methods Used in Digital Storybook Learning in EFL Classroom: A Systematic Literature Review - Ni Luh Putu Devi Puspitasari; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (Journal of English Language and Education, 2026)
While digital storybooks are increasingly popular in language classrooms, there is still a lack of consensus on which specific instructional methods yield the most effective learning outcomes. This systematic literature review aims to identify instructional methods used in digital storybook-based learning and examine the learning outcomes associated with each approach. Following the PRISMA 2020 guidelines, this review systematically searched five specific academic databases (Google Scholar, ERIC, ScienceDirect, SAGE Journals, and Taylor Francis) covering studies published between 2021 and 2026. Twelve studies met the inclusion criteria for qualitative analysis. The findings reveal three main instructional approaches: task- and project-based learning, multimodal and technology-enhanced learning, and interaction- and support-based learning. These approaches are consistently associated with positive cognitive and affective outcomes. Overall, this review demonstrates that digital storybooks are most effective when integrated with appropriate, student-centered, and interactive pedagogical strategies rather than used as stand-alone reading tools.